Estimating the effects of teen motherhood in Chile: a family fixed effects approach - Berthelon, Matías; Kruger, Diana; Eberhard, Juan P. (Estudios de Economía, 2017)
We study the effect of adolescent motherhood on education and labor outcomes among 20-24 year old women in Chile. We identify causal effects of motherhood with family fixed effects using a large data set covering the 1990-2011 period. Teen motherhood has negative effects on education and labor outcomes, and timing of motherhood matters: teen births reduce education outcomes, while young motherhood reduces labor force participation. Labor outcome effects are present among the non-poor, and effects changed between 1990 and 2011. Results highlight the important role of adolescent motherhood in women’s human capital accumulation and income inequality.